Nucleus accumbens local circuit for cue-dependent aversive learning - Andrew Belilos; Cortez Gray; Christie Sanders; Destiny Black; Elizabeth Mays; Christopher Richie; Ayesha Sengupta; Holly Hake; T. Chase Francis (Cell Reports, 2023)
Summary: Response to threatening environmental stimuli requires detection and encoding of important environmental features that dictate threat. Aversive events are highly salient, which promotes associative learning about stimuli that signal this threat. The nucleus accumbens is uniquely positioned to process this salient, aversive information and promote motivated output, through plasticity on the major projection neurons in the brain area. We describe a nucleus accumbens core local circuit whereby excitatory plasticity facilitates learning and recall of discrete aversive cues. We demonstrate that putative nucleus accumbens substance P release and long-term excitatory plasticity on dopamine 2 receptor-expressing projection neurons are required for cue-dependent fear learning. Additionally, we find that fear learning and recall is dependent on distinct projection neuron subtypes. Our work demonstrates a critical role for nucleus accumbens substance P in cue-dependent aversive learning.